2007
DOI: 10.1074/jbc.m610146200
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Precursor Protein and Presenilin1 Interact with the Adaptor GRB2 and Modulate ERK 1,2 Signaling

Abstract: The amyloid precursor protein (APP) and the presenilins 1 and 2 are genetically linked to the development of familial Alzheimer disease. APP is a single-pass transmembrane protein and precursor of fibrillar and toxic amyloid-␤ peptides, which are considered responsible for Alzheimer disease neurodegeneration. Presenilins are multipass membrane proteins, involved in the enzymatic cleavage of APP and other signaling receptors and transducers. The role of APP and presenilins in Alzheimer disease development seems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 78 publications
3
74
0
1
Order By: Relevance
“…200 Interestingly, Grb2 also binds presenilin 1 (PS1), which is involved in cleavage of APP. 201 Grb2, APP and PS1 reportedly associate at the centrosome, where the complex targets extracellular signal-related kinases 1 and 2 signalling. 201 Finally, it is particularly intriguing that robust interactions between Grb2 and ErbB receptors have been demonstrated.…”
Section: Disc1 Interaction With Grb2mentioning
confidence: 99%
See 1 more Smart Citation
“…200 Interestingly, Grb2 also binds presenilin 1 (PS1), which is involved in cleavage of APP. 201 Grb2, APP and PS1 reportedly associate at the centrosome, where the complex targets extracellular signal-related kinases 1 and 2 signalling. 201 Finally, it is particularly intriguing that robust interactions between Grb2 and ErbB receptors have been demonstrated.…”
Section: Disc1 Interaction With Grb2mentioning
confidence: 99%
“…201 Grb2, APP and PS1 reportedly associate at the centrosome, where the complex targets extracellular signal-related kinases 1 and 2 signalling. 201 Finally, it is particularly intriguing that robust interactions between Grb2 and ErbB receptors have been demonstrated. ErbB receptors bind neuregulin and are thus already suspected to be involved in molecular pathways that underlie some cases of severe psychiatric illness (for a review, see Corfas et al 202 ).…”
Section: Disc1 Interaction With Grb2mentioning
confidence: 99%
“…The only exception to this is Shc, which requires the phosphorylation of Tyr682 for binding to APP [21,29]. Tyr682 phosphorylation is also necessary for the binding of APP to the SH2 domains of Abl and Grb2, and might regulate downstream signal transduction cascades [29,30]. Structural studies have revealed that the binding interface of APP and the PTB domain of X11 involves residues within the GYENPTY motif [31].…”
Section: The Cytoplasmic Domain Of App and Its Binding Proteinsmentioning
confidence: 99%
“…2E). Previous studies have suggested that APP can influence ERK and/or Akt activation (Nizzari et al, 2007; Lee et al, 2009). We observed decreased ERK‐1 and ‐2 phosphorylation at 24, 48, and 72 h after siRNA‐mediated knockdown of APP in NSCLC cell lines A549 and H1299 (Fig.…”
Section: Resultsmentioning
confidence: 98%